Entrepreneurship in agriculture and healthcare: Different entry strategies of care farmers. (February 2016) - Hassink, Jan; Hulsink, Willem; Grin, John
Abstract: Care farming provides an interesting context of multifunctional agriculture where farmers face the challenge of having to bridge the gap between agriculture and healthcare and acquire new customers, partners and financial resources from the care sector. We compared different entry strategies of different types of care farmers: varying in weak and strong multi-functionality, the degree of legitimacy and background of the initiator. Our objective is to provide insight into the key factors contributing to the development and success of care farms, in particular by focusing on the role of entrepreneurship, commitment and the ability to cope with barriers in the environment. We developed a framework based on entrepreneurship and opportunity structure. We interviewed different types of care farmers. Many of them were farmers' spouses with prior experience in the care sector. Entrepreneurship and the local and national opportunity structure, like (changes in) financing regulations, interact and explain the accessibility and growth potential of care farms. Pioneers in the emerging care farming sector faced a lack of cognitive and sociopolitical legitimacy and a mismatch with incumbent financing structures. Initially, they only succeeded with sufficient levels of entrepreneurial behavior and commitment. Having a professional background and network in the care sector was helpful in the starting phase. Later entrants experienced more legitimacy and fewer barriers as financing regulations had changed. They had different entry options: being independent or under supervision of a care organization or a regional support organization of care farms. For this latter option, newcomer problems were solved by established care organizations. However, there was a risk of becoming too dependent on established care organizations. Initiatives with weak multi-functionality failed more often than initiatives with strong multi-functionality due to unrealistic expectations and limited commitment on the part of initiators. Highlights: Pioneers needed exceptional entrepreneurial behavior to be successful. Later entrants benefited from increased legitimacy, financing structures and support. Later entrants had more entry options than pioneers. Many farmers' spouses had a hybrid professional identity which was helpful to initiate a care farm. Initiatives with weak multi-functionality failed more often than those with strong multi-functionality.